Métis families and schools : the decline and reclamation of Métis identities in Saskatchewan, 1885-1980 - Anuik, Jonathan David (2009)
In the late-nineteenth century, Métis families and communities resisted what they perceived to be the encroachment of non-Aboriginal newcomers into the West. Resistance gave way to open conflict at the Red River Settlement and later in north central Saskatchewan. Both attempts by the Métis to resist the imposition of the newcomer’s settlement agenda were not successful, and the next 100 years would bring challenges to Métis unity. The transmission of knowledge of a Métis past declined as parents and grandparents opted to encourage their children and youth to pass into the growing settler society in what would become Saskatchewan. As parents restricted the flow of Métis knowledge, missionaries who represented Christian churches collaborated to develop the first Northwest Territories Board of Education, the agent responsible for the first state-supported schools in what would become the province of Saskatchewan. These first schools included Métis students and helped to shift their loyalties away from their families and communities and toward the British state. However, many Métis children and youth remained on the margins of educational attainment. They were either unable to attend school, or their schools did not have the required infrastructure or relevant pedagogy and curriculum. In the years after World War II, the Government of Saskatchewan noticed the unequal access to and achievement of the Métis in its schools. The government attempted to bring Métis students in from the margins through infrastructural, pedagogical, and curricular adaptations to support their learning. Scholars have unearthed voluminous evidence of missionary work in Canada and have researched and written about public schools. As well, several scholars have undertaken research projects on Status First Nations education in the twentieth century. However, less is known about Métis’ interactions with Christian missionaries and in the state-supported or publicly funded schools. In this dissertation, I examine the history of missions and public ...